2022
DOI: 10.1136/bmjopen-2021-058135
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal depression and anxiety with toddler social-emotional and cognitive development in South Africa: a prospective cohort study

Abstract: ObjectiveA robust literature has identified associations between prenatal maternal depression and adverse child social-emotional and cognitive outcomes. The majority of prior research is from high-income countries despite increased reporting of perinatal depression in low/middle-income countries (LMICs). Additionally, despite the comorbidity between depression and anxiety, few prior studies have examined their joint impact on child neurodevelopment. The objective of the current analysis was to examine associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…While many of the studies originate from Europe, North America, and Australia, similar ndings have been reported in other regions (13,(21)(22)(23)(24)(25). In one South African study, three-year-old children born to mothers experiencing both depression and anxiety during pregnancy faced a higher risk of emotional di culties compared to their counterparts born to mothers experiencing only one of these issues; children born to mothers without these symptoms were found to be at the lowest risk (22). Overall, across different data sources and populations, the evidence for an observational association between maternal prenatal stress and offspring outcomes is quite consistent(26).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…While many of the studies originate from Europe, North America, and Australia, similar ndings have been reported in other regions (13,(21)(22)(23)(24)(25). In one South African study, three-year-old children born to mothers experiencing both depression and anxiety during pregnancy faced a higher risk of emotional di culties compared to their counterparts born to mothers experiencing only one of these issues; children born to mothers without these symptoms were found to be at the lowest risk (22). Overall, across different data sources and populations, the evidence for an observational association between maternal prenatal stress and offspring outcomes is quite consistent(26).…”
Section: Introductionsupporting
confidence: 75%
“…For example, one US study that analyzed data from three different pregnancy cohorts found a relationship between maternal stress during pregnancy and emotional issues in offspring observed at ages 8 to 9 years (15). While many of the studies originate from Europe, North America, and Australia, similar ndings have been reported in other regions (13,(21)(22)(23)(24)(25). In one South African study, three-year-old children born to mothers experiencing both depression and anxiety during pregnancy faced a higher risk of emotional di culties compared to their counterparts born to mothers experiencing only one of these issues; children born to mothers without these symptoms were found to be at the lowest risk (22).…”
Section: Introductionmentioning
confidence: 82%
“…Between April 2018 and March of 2020, participants were recruited from the Bishop Lavis community at their Health Center or the Diabetes Clinic in Tygerberg Academic Hospital in the Western Cape Province, South Africa. This study was built on existing collaborations with the university through the Safe Passage Study [19]. Results from the Safe Passage study revealed high rates of depression and anxiety within the population: 55% of mothers had a prenatal Edinburgh postnatal depression score (EPDS) � 13 and 19.17% of mothers had a State-Trait Anxiety Inventory (STAI) � 40 [19].…”
Section: Populationmentioning
confidence: 99%
“…This study was built on existing collaborations with the university through the Safe Passage Study [19]. Results from the Safe Passage study revealed high rates of depression and anxiety within the population: 55% of mothers had a prenatal Edinburgh postnatal depression score (EPDS) � 13 and 19.17% of mothers had a State-Trait Anxiety Inventory (STAI) � 40 [19].…”
Section: Populationmentioning
confidence: 99%